High-performance polyamide thin-film-nanocomposite reverse osmosis membranes containing hydrophobic zeolitic imidazolate framework-8 - Duan, Jintang; Pan, Yichang; Pacheco, Federico; Litwiller, Eric; Lai, Zhiping; Pinnau, Ingo (Journal of membrane science, 2015)
A hydrophobic, hydrothermally stable metal-organic framework (MOF) - zeolitic imidazolate framework-8 (ZIF-8) was successfully incorporated into the selective polyamide (PA) layer of thin-film nanocomposite (TFN) membranes for water desalination. The potential advantages of ZIF-8 over classic hydrophilic zeolite used in TFNs include: i) theoretically faster water transport within the framework and ii) better compatibility with the PA matrix. The TFN membranes were characterized with SEM, TEM, AFM, XPS, water contact angle measurements and reverse osmosis tests under 15.5bar hydraulic pressure with 2000ppm NaCl solution. Lab-made, nano-sized (~200nm) ZIF-8 increased water permeance to 3.35±0.08L/m2·h·bar at 0.4% (w/v) loading, 162% higher than the pristine PA membranes; meanwhile, high NaCl rejection was maintained. The TFN surface was less crosslinked and more hydrophilic than that of the pristine PA. A filler encapsulation mechanism was proposed for the effects of filler on TFN membrane surface morphology and properties. This study experimentally verified the potential use of ZIF-8 in advanced TFN RO membranes. [Display omitted] •ZIF-8-based TFN membranes were successfully prepared.•Lab-made, nano-sized ZIF-8 increased water flux up to 162%.•ZIF-8 exhibited no adverse effect on NaCl rejection.